2017
DOI: 10.23937/2469-5718/1510061
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Levels and Their Relation to the Severity of Chronic Obstructive Pulmonary Disease in Patients Who Underwent Pulmonary Rehabilitation Program

Abstract: Chronic obstructive pulmonary disease is a preventable and treatable disease characterized by persistent airflow limitation, usually progressive and associated with an abnormal lung inflammatory response to inhalation of particles or toxic gases. Exacerbations and comorbidities contribute to the overall worsening of the patient. The aim of this study was to assess the anxiety and depression levels and their relation to disease severity, in addition to analyzing the correlation between anxiety and depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although several factors have been proposed to contribute to poor functional performance in COPD patients [11][12][13], the effects of psychological factors, such as anxiety and depression, on physical performance and the overall health status of COPD patients is controversial. Some studies have shown that anxiety and depression negatively impact physical functioning among patients with COPD [14,15], while another study found that the levels of anxiety and depression of COPD patients were not correlated with the distance walked during functional performance tests [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although several factors have been proposed to contribute to poor functional performance in COPD patients [11][12][13], the effects of psychological factors, such as anxiety and depression, on physical performance and the overall health status of COPD patients is controversial. Some studies have shown that anxiety and depression negatively impact physical functioning among patients with COPD [14,15], while another study found that the levels of anxiety and depression of COPD patients were not correlated with the distance walked during functional performance tests [16].…”
Section: Introductionmentioning
confidence: 99%